Psychiatry and Neuroscience Update - Vol. II : A Translational Approach - Gargiulo, Pascual Ángel; Mesones-Arroyo, Humberto Luis (Springer International Publishing : Imprint: Springer, 2017)
The aim of this unique book is to provide an overview of recent advances bridging the gap between psychiatry and neuroscience, allowing a fruitful dialogue between both sciences. The emerging interactions and mutual contributions between neuroscience and psychiatry are here recognized. This book is designed to identify the borders, trends and implications in both fields today. Comprehensive and developed by a renowned group of experts from both fields, the book is divided into four parts: Epistemological Considerations About the Study of Normal and Abnormal Human Behaviors; From Basic Neurosciences to Human Brain; Neurosciences, Learning, Teaching and the Role of Social Environment; and Explaining Human Pathological Behaviors: From Brain Disorders to Psychopathology. A unique and invaluable addition to the literature in psychiatry and neuroscience, Psychiatry and Neuroscience Update - Vol. II: A Translational Approach offers an important and clearer understanding of the relationship between these two disciplines. This book is directed to students, professionals and researchers of medicine, psychology, psychopedagogy and nursery.
Keywords: Medicine.; Neurosciences.; Internal medicine.; Neurology.; Psychiatry.; Clinical psychology.; elektronické knihy; electronic books